THE CONSTRUCTION OF CITIZENSHIP CHARACTER THROUGH LEARNING BASED-LOCAL EXCELLENCE IN SENIOR HIGH SCHOOL 1 PANGANDARAN - Kokom Komalasari, Rosidah, Dasim Budimansyah, (Jurnal Civicus, 2014)
Education is an alternative for solving many kind of problems that happen in Indonesia and have a central position because the target of education is to improve human resource. The character problem right now became very important problem for education. Because in reality young generation right now having a degradation of character. In their effort to find a way to building civic disposition, this research is discussed about character building for citizenship thorough education based excellence local based learning that have been implementation at SMAN 1 Pangandaran. This researcher used qualitative approach with studies case method model exploratory. The result of this researcher show that implementation education superiority local based is capable to build civic disposition for student.